2017
DOI: 10.1007/s12639-017-0950-2
|View full text |Cite
|
Sign up to set email alerts
|

Free-living amoebae in the water resources of Iran: a systematic review

Abstract: Free-living amoebae (FLA) are a group of protozoa with the capabilities of growth in the environment and invasion to the human body which have been isolated from different water sources. ,, and are the most important FLA. These cause a variety of severe complications of eye and central nervous system. Despite the fact that various studies have demonstrated the prevalence of FLA in different parts of Iran, there is no comprehensive evaluation and conclusion regarding the pollution of various water sources in Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Microenvironment differences in microbiota modulation were more evident on the supergroup Amoebozoa. They are a highly diverse group of phagotrophic protists that includes species characterized as free-living amoeba (FLA) ( Saburi et al., 2017 ). The life forms of these microorganisms include cysts ( Sriram et al., 2008 ), which are resistance forms that favor dispersion and its perpetuation in singular environments.…”
Section: Discussionmentioning
confidence: 99%
“…Microenvironment differences in microbiota modulation were more evident on the supergroup Amoebozoa. They are a highly diverse group of phagotrophic protists that includes species characterized as free-living amoeba (FLA) ( Saburi et al., 2017 ). The life forms of these microorganisms include cysts ( Sriram et al., 2008 ), which are resistance forms that favor dispersion and its perpetuation in singular environments.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of these reports, the most prevalent Acanthamoeba genotype was T4 in water sources, comprising 62.96%, 91.7%, 83.3%, and 71.6% of water source samples from Shiraz [8], Tehran [30], Mazandaran [31], and Ahvaz [5], respectively. Also, the results of a systematic review showed that Acanthamoeba genotypes T4, T5, and T2 comprised 39%, 17%, and 16% of Acanthamoeba in water sources of Iran, respectively [32].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no reports of microbial contamination of toys, including rubber ducks, used in bathing facilities in Japan, though the bathing is very common among the Japanese. Free-living amoebae are widely distributed in the aquatic environment and have been isolated from bathtub water, drinking water, and river water (Zbikowska et al 2013, Shaheen et al 2019, Saburi et al, 2017, Edagawa et al 2009) . Free-living amoebae serve as hosts for bacteria such as Legionella, Escherichia coli, Mycobacterium avium and P. aeruginosa, provide a breeding ground for a variety of bacteria (Greub et al, 2004) , and are frequently detected in biofilms in the environment (Shaheen et al, 2019, Taravaud et al, 2018 .…”
Section: Microbial Contamination Inside Rubber Ducksmentioning
confidence: 99%